Arsenic load in rice ecosystem and its mitigation through deficit irrigation. (15th July 2017) - Mukherjee, Arkabanee; Kundu, M.; Basu, B.; Sinha, B.; Chatterjee, M.; Bairagya, M. Das; Singh, U.K.; Sarkar, S.
Abstract: Rice the staple food is a notable intake source of arsenic to the rural population of eastern India through food-chain. A field survey was carried out to study the variation of arsenic load in different parts of rice genotype Shatabdi (most popular genotype of the region) exposed to varying level of arsenic present in the irrigation water and soil. As irrigation is the primary source of arsenic contamination, a study was conducted to assess arsenic load in rice ecosystem under deficit irrigation practices like intermittent ponding (IP), saturation (SAT) and aerobic (AER) imposed during stress allowable stage (16–40 days after transplanting) of the crop (genotype Shatabdi). Present survey showed that arsenic content in water and soil influenced the arsenic load of rice grain. Variation in arsenic among different water and soil samples influenced grain arsenic load to the maximum extent followed by straw. Deviation in root arsenic load due to variation in water and soil arsenic content was lowest. Arsenic concentration of grain is strongly related to the arsenic content of both irrigation water and soil. However, water has 10% higher impact on grain arsenic load over soil. Translocation of arsenic from root to shoot decreased with the increase in arsenic content of water. Imposition of saturated and aerobic environment reduced both yield and grain arsenic load. In contrast under IP a marked decrease in grain arsenic content recorded with insignificant reduction in yield. Deficit irrigation resulted in significant reduction (17.6–25%) in arsenic content of polished rice and the values were lower than that of the toxic level (<0.2 mg kg −1 ). In contrast the decrease in yield was to the tune of 0.9% under IP regime over CP. Highlights: At low As exposure level, rice roots effectively restrict entry of As into plant. Transport of As from root to straw varies inversely with its exposure level. Deficit irrigation can restrict the As content of white rice within 200 μg kg −1 . Intermittent ponding reduces As load without significant variation in grain yield.